A Legal Commentary on the Position of Liquidated Ascertained Damages in the United Kingdom - Balasingam, Usharani (INTI Publishing House Sdn. Bhd., 2006)
The purpose of this paper is to consider the various aspects of a liquidated agreed damages clause (LAD) in contracts, from the perspective of recent English case-laws in the United Kingdom. The focus is on the law on penalty generally in terms of its principles and criteria that are needed for a clause to be a valid LAD clause, the rationale for parties to agree to such a LAD clause and the effects of a LAD clause in a contract. The definition, use and implication of exclusion clauses and limitation clauses are also considered. The purpose of this paper is moreover to focus the mind of contracting parties on the legal considerations as to the nature and effect of such clauses. Better understanding of the legal implications of such clauses would place the parties in a better position to negotiate and protect their own interests. Recommendations and safeguards are suggested for the benefit of the contracting parties.